2020
DOI: 10.1007/s00784-020-03344-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes after uncomplicated and complicated crown fractures in permanent teeth

Abstract: Objectives The objectives of this retrospective clinical study were to describe characteristics of crown fractures in permanent teeth and to investigate the survival of pulp vitality and restorations in uncomplicated and complicated crown fractures. Materials and methods This retrospective study collected information from patients suffering from dental trauma who were treated between January 2004 and June 2017. The study population consisted of 434 patients (253 males/181 females; mean age 20.7 years) with 489… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
25
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 30 publications
9
25
2
1
Order By: Relevance
“…In contrast to VPT of cariously exposed pulps where HCSCs clearly outperform calcium hydroxide in terms of clinical success (ESE, 2019b), in the treatment of traumatically exposed pulps, the capping material (calcium hydroxide vs. HCSC) does not seem to be a decisive factor (Bissinger et al, 2021; Dammaschke et al, 2019a). A retrospective study demonstrated a significantly higher success rate when a new generation of HSCS was used instead of calcium hydroxide, however the latter still achieved a clinical success rate of 93% (Rao et al, 2020).…”
Section: Endodontic Management Of the Traumatically Exposed Pulp: Pre...mentioning
confidence: 99%
“…In contrast to VPT of cariously exposed pulps where HCSCs clearly outperform calcium hydroxide in terms of clinical success (ESE, 2019b), in the treatment of traumatically exposed pulps, the capping material (calcium hydroxide vs. HCSC) does not seem to be a decisive factor (Bissinger et al, 2021; Dammaschke et al, 2019a). A retrospective study demonstrated a significantly higher success rate when a new generation of HSCS was used instead of calcium hydroxide, however the latter still achieved a clinical success rate of 93% (Rao et al, 2020).…”
Section: Endodontic Management Of the Traumatically Exposed Pulp: Pre...mentioning
confidence: 99%
“…Cvek 23 found that all cases of PN after partial pulpotomy could be diagnosed within 26 months following treatment and he proposed the need for a 3‐year follow‐up period. Similarly, Bissinger et al 19 reported that the mean time interval for PN was 280.9 days (9.2 months), and most cases of PN occurred within the first 2 years after the injury. The IADT recommends clinical and radiographic evaluations after 6–8 weeks, 3, 6 months and 1 year 1 .…”
Section: Discussionmentioning
confidence: 87%
“…Reattachment of tooth fragments provides a conservative, aesthetic and cost‐effective restorative option. Furthermore, reattachment of the fragment does not affect pulp outcomes in the management of CCF 19 . Andreasen et al 20 reported retention rates of 20% and 25% after 7.5 and 10.5 years, respectively, for rebonded fragments.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] A common endodontic complication is the loss of pulp vitality, which was more prevalent in patients with additional luxation. [13] In this cross-sectional study 359 patients of both genders with 525 permanent teeth were presented. Patients were aged between 7-12 years with mean age 8.64 ±12.37 years.…”
Section: Discussionmentioning
confidence: 99%